2012
DOI: 10.1002/app.37821
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of strongly acidic ion‐exchange catalysts and the desulfonation study in the isobutylene dimerization reaction

Abstract: Three commercial ion-exchange resin based catalysts were compared under different temperature and liquid-volume hourly space velocity (LHSV) in the isobutene (IB, C4) dimerization reaction using a plug flow reactor in the absence of any selectivity enhancing component. High IB conversion for all catalysts was obtained at or higher than 50 C. But, diisobutene (DIB, C8) selectivity decreased with the increase of temperature. High C8 selectivity was observed with LHSV higher than 1.5 at 50 C. The best catalytic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…This indicates that desulphonation is significant under the reaction conditions. Water is one of the products of the reaction and it helps in creating a polar environment around the catalyst surface, conducive for desulphonation, 24 and more importantly, the presence of metal ions may trigger hydrolysis of sulphonic acid group leading to desulphonation accordingly to previous studies 31 . It may be noted that in the absence of metal impurities when the reaction was performed in a glass reactor, the change in site density, and hence the sulphur content, was insignificant in both reactive (4.2 meq/g from 4.7 meq/g in 120 h in 72 h) and non‐reactive environments (4.5 meq/g from 4.7 meq/g in 130 h).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This indicates that desulphonation is significant under the reaction conditions. Water is one of the products of the reaction and it helps in creating a polar environment around the catalyst surface, conducive for desulphonation, 24 and more importantly, the presence of metal ions may trigger hydrolysis of sulphonic acid group leading to desulphonation accordingly to previous studies 31 . It may be noted that in the absence of metal impurities when the reaction was performed in a glass reactor, the change in site density, and hence the sulphur content, was insignificant in both reactive (4.2 meq/g from 4.7 meq/g in 120 h in 72 h) and non‐reactive environments (4.5 meq/g from 4.7 meq/g in 130 h).…”
Section: Resultsmentioning
confidence: 99%
“…It is generally believed that desulphonation happens at high temperature leading to release of 4‐phenol sulphonic acid from the polymer matrix by oxidation 23,30 . Since the temperatures employed in cation‐exchange resin catalysed reactions are less than 393 K, barring some exceptions, 24 desulphonation is normally not considered as a major cause of deactivation. However, in a recent study 31 reported for water purification by similar sulphonic acid resins, it has been revealed that the counter ions may promote hydrolysis of sulphonic acid group leading to formation of corresponding salt and the relative neutral aromatic ring as shown in Scheme 2.…”
Section: Different Sources Of Catalyst Deactivationmentioning
confidence: 99%
See 1 more Smart Citation
“…Solid phosphoric acid catalyst has high catalytic activity and is used widely in industry, but it has low mechanical strength, no selectivity and no regeneration. Acidic cation resin catalyst has the characteristics of high acidity, stable catalytic effect, low price, mild reaction conditions and a single product, but it is difficult to regenerate 22 . Molecular sieve catalysts have the advantages of shape‐selective catalysis, environmental friendliness, high stability and reproducibility 23,24 .…”
Section: Introductionmentioning
confidence: 99%